Mechanical formulation of helmholtz's thermodynamics (2013)
In the nineteenth century, the mechanistic idea of natural phenomena had been consolidated to the point of believing that it was possible to explain all the physical from the mechanical theory. In this paper we show how thermodynamics is influenced by this prejudice, beginning with the fundamental hypothesis that motivated and led Helmholtz to give a mechanical interpretation of the principles of thermodynamics based on the mechanical model of unicycles that finally loses relevance when entering crisis the mechanistic model of the natural world.